Do Social Networking Sites Influence Well-Being? The Extended Active-Passive Model. (February 2022) - Verduyn, Philippe; Gugushvili, Nino; Kross, Ethan
Do social networking sites (SNSs) influence well-being? According to the active-passive model of SNS use, the impact of SNSs on well-being depends on how they are used: Using SNSs actively to interact with other users positively affects well-being, whereas passive consumption of SNS content negatively affects well-being. However, emerging evidence suggests that the active-passive distinction is too coarse to fully capture the relationship between SNS use and well-being. Here we describe the extended active-passive model of SNS use, which refines the original model in three ways: It decomposes active use, decomposes passive use, and crosses usage types with user characteristics. We describe recent empirical evidence illustrating the benefits of these three extensions and highlight important future research directions. The extended active-passive model of SNS use provides a nuanced understanding of the relationship between SNS use and well-being by highlighting that active use of SNSs is not always beneficial and passive use is not always detrimental.